ANALISIS PENGARUH PELAYANAN TERHADAP KEPUASAN KONSUMEN MENGGUNAKAN METODE SERVICE QUALITY DAN SERVICE BLUEPRINT PADA JNE CABANG YOGYAKARTA (Studi Kasus: JNE VIBRO MANDIRI) - Pranata, Aditia; Wibowo, Agus Hindarto; Yusuf, Muhammad (Prodi Teknik Industri, Universitas AKPRIND Indonesia, 2023)
PT Jalur Nugraha Ekurir (JNE) is a company engaged in the field of freight forwarding services. because now there are many companies engaged in the same field, JNE must be more careful in responding to this competition. One way to do this is to evaluate the company's performance by measuring the quality of services provided by consumers, namely by analyzing customer satisfaction. Solving the problem used to measure service quality in this research, is to use the service quality method. In order to be able to provide a visual picture and help identify service delivery systems and provide a clear picture of consumer activities in receiving these services, the service blueprint method is used.Based on the identification of the quality of service at PT Jalur Nugraha Ekurir (JNE) which includes 5 dimensions with a total of 25 questionnaire attributes, it can be seen that the value of the quality of service per dimension with a very satisfactory value there are only a few points that must be improved in terms of service. The technical response that is prioritized for improvement in an effort to improve the quality of JNE services is to provide more training for employees so that they can serve consumers even better so that the quality of service felt by consumers feels very satisfied.